Open-set web genre identification - Pritsos, Dimitrios; Πρίτσος, Δημήτριος (2020)
World wide web is constantly increasing and people use information in web-pages for everyday activities. There is an emerging need for facilitating access in this huge repository in a seamless way that is in accordance with users' understanding. Genre is an important factor to characterize the properties of web-pages. Web genres (e.g., blogs, e-shop, FAQs, etc.) refer to the form, structure, and communicative purpose of web-pages rather than their topic. Web Genre Identification (WGI) provides a means to improve effectiveness of information retrieval systems by allowing sophisticated queries combining topic and genre information and ranking/grouping search results according to genre. Specialized document collections can be compiled by adopting genre-aware focused crawling. The credibility assessment of web-pages can be significantly enhanced given that information about their genre is available. Cyber-security applications like anti-phishing can also be enhanced by incorporating genre of web-pages. In case natural language technology tools should be applied to the textual part of web-pages, knowing their genre allows the selection of appropriate tools that have been trained to handle similar documents.